The Management Theory Jungle - Koontz, Harold (Academy of Management Journal, 1961)
Focuses on the varying approaches to management theory by discussing major schools of management theory. Management process school; Empirical school; Human behavior school; Social system school; Decision theory school; Mathematical school.